Comparison Between Phenomenological and Fiber-Section Non-linear Models - Terrenzi, Marco; Spacone, Enrico; Camata, Guido (Frontiers in Built Environment, 2020)
The prediction of the seismic response of structures requires accurate models for describing the behavior of each structural element. In frame analysis, non-linearities are typically modeled through either lumped or distributed plasticity elements. Another important assumption is needed for the selection of the appropriate section model. Phenomenological laws for the section behavior are computationally faster but less accurate than fiber-section models. This study compares the predictions obtained for reinforced concrete sections and simple single columns with a phenomenological section law (combined with a lumped plasticity element) and with a fiber-section model (combined with a distributed plasticity element). The phenomenological section model is that proposed by Ibarra et al. (2005) with the predictive equations used by Haselton et al. (2008). The fiber section distributed element is that by Spacone et al. (1996a,b). Comparisons show some important differences in the section responses (particularly for high levels of axial load) and in predicting the responses of experimentally tested columns.